Exploring the Relationship between Lifelong Learning Components and Evidence- Based Medicine Acceptance among Physiopathology Students at Mazandaran University of Medical Sciences, 2023 - Parinaz Talebi; Nassim Ghahrani; Forouzan Sadeghimahalli; Siavash Moradi (Journal of Mazandaran University of Medical Sciences, 2024)
Background and purpose: Lifelong learning is a cornerstone of the medical profession, ensuring that specialists remain current with developments in their field. Given this importance, this study investigated the relationship between lifelong learning and its components with the acceptance of evidence based medicine among physiopathology students at Sari Medical School, Mazandaran University of Medical Sciences, during the year 2023. Materials and methods: This descriptive-correlational study included 170 physiopathology students, selected through a convenience sampling method. Data collection was conducted using two questionnaires: the first assessed lifelong learning through 14 items across three subscales; beliefs related to learning and motivation, information search skills, and attention to learning opportunities. The second questionnaire measured the acceptance of evidence-based medicine. Data were entered into SPSS V.21 for analysis, employing descriptive and inferential statistical methods, including correlation tests, to evaluate the findings. Results: The average lifelong learning score in this study was 38.61±4.37, placing it in the high range (above 36). The mean score for the subscales: beliefs related to learning and motivation, information search skills, and attention to learning opportunities were 20.78±2.61, 10.34±1.86, and 7.49±1.57, respectively. The overall evidence-based acceptance score was 34.51±6.08, also categorized as high (above 33). Among the components of lifelong learning, only the information search skill subscale showed a significant positive correlation with the evidence-based medicine acceptance score. Conclusion: Despite the high levels of both lifelong learning orientation and acceptance evidence based medicine observed in this study, no significant positive association was found between them. Therefore, to enhance students’ lifelong learning orientation, it is essential to adopt strategies that focus on developing information management skills and fostering an environment that supports the evidence-based learning